2020
DOI: 10.1101/2020.01.22.914952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of a novel coronavirus associated with the recent pneumonia outbreak in humans and its potential bat origin

Abstract: Since the SARS outbreak 18 years ago, a large number of severe acute respiratory syndrome related coronaviruses (SARSr-CoV) have been discovered in their natural reservoir host, bats1-4. Previous studies indicated that some of those bat SARSr-CoVs have the potential to infect humans5-7. Here we report the identification and characterization of a novel coronavirus (nCoV-2019) which caused an epidemic of acute respiratory syndrome in humans, in Wuhan, China. The epidemic, started from December 12th, 2019, has ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
730
0
36

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 663 publications
(796 citation statements)
references
References 13 publications
15
730
0
36
Order By: Relevance
“…Therefore, we suggest that 2019-nCoV might use ACE2 as the receptor, despite the presence of amino acid mutations in the 2019-nCoV receptor-binding domain. Although a previous study using HeLa cells expressing ACE2 proteins showed that 2019-nCoV could employ the ACE2 receptor, 37 whether these mutations affect ACE2 binding or change receptor tropism requires further study.…”
Section: Sars-covmentioning
confidence: 99%
“…Therefore, we suggest that 2019-nCoV might use ACE2 as the receptor, despite the presence of amino acid mutations in the 2019-nCoV receptor-binding domain. Although a previous study using HeLa cells expressing ACE2 proteins showed that 2019-nCoV could employ the ACE2 receptor, 37 whether these mutations affect ACE2 binding or change receptor tropism requires further study.…”
Section: Sars-covmentioning
confidence: 99%
“…Despite drastic containment measures, the spread of 2019-nCoV, now officially known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is ongoing. Phylogenetic analysis of this virus indicated that it is different (~80% nucleotide identity) but related to SARS-CoV-1 [15]. Because the world is threatened by the possibility of a SARS-CoV-2 pandemic, the broad-spectrum antiviral effects of chloroquine warranted particular attention for repurposing this drug in the therapy of the disease caused by SARS-CoV-2, named coronavirus disease 2019 (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…On December 12th, 2019, the Wuhan Municipal Health Commission (WMHC) in the People's Republic of China reported 27 human cases of viral pneumonia, 7 of them seriously ill. All had a shared exposure in the Huanan Seafood Wholesale Market, where farm animals, bats, and snakes were also sold [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These are important pathogens of humans and other vertebrates. They can infect the respiratory, gastrointestinal, hepatic and central nervous system tracts of man, cattle, birds, bats [2], rodents and various wild animals [10]. Coronaviruses, like influenza viruses, circulate in nature in various animal species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation